Collaborative Management Of Islamic Education and Technology For Improving The Competence Of Students In The Digital Era - Widodo, Wahyudi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to analyze the management of collaboration between Islamic education and technology in improving the competence of students at the Miftahul Huda Gading Malang Islamic Boarding School in the digital era. In the face of rapid technological advancements, it is important for Islamic boarding schools to integrate technology in the learning process and daily life. This study uses a qualitative approach with a case study method to explore how the Miftahul Huda Gading Malang Islamic Boarding School manages the integration of technology in Islamic education. The results of the study show that the implementation of good collaboration management produces students who not only understand the teachings of Islam, but are also skilled in the use of technology. The students acquire digital skills such as graphic design, website creation, and social media management, which they can apply in their daily lives and professional careers in the future. This study concludes that effective collaboration between Islamic education and technology can produce students who have technical skills as well as a deep understanding of religion, as well as prepare them to face global challenges in the digital era. Evidence shows that pesantren graduates qualify to become lecturers, teachers, journalists, photographers, technology technicians, programmers, etc.